Efeito imediato e mediato da acupuntura no tratamento de pacientes portadores da Síndrome de Apnéia Obstrutiva do Sono - Sugai, Gisele Cristina Machado [UNIFESP] (2009)
STUDY OBJECTIVES: 1 - To investigate the immediate (single session) and mediate (ten sessions) effect of acupuncture over the sleep pattern of patients with moderate obstructive sleep hypopnea apnea (OSHA). 2 - To compare manual acupuncture (MA) and electroacupuncture (EA) with different stimulation frequencies (2 Hz and 10 Hz). 3 - To determine the role of endogenous serotonin in this mechanism. SETTING: Department of Physiology, Sleep Division of Department of Psychobiology, Chinese Medicine Division and Department of Nephrology, Federal University of São Paulo, Brazil. INTERVENTIONS: Acupuncture applied in true acupoints accompanied by needle manipulations or electroacupunture 2 hz and 10 Hz for 30 minutes in all patients, except control group pacients. DESIGN: In a randomized, placebo-controlled and single blind study, fourty-three patients with an apnea-hypopnea index (AHI) of 15 to 30 per hour were randomly assigned to 4 groups: control group, MA group, EA 2Hz group and EA 10Hz group. The control group received no intervention. The MA group, EA 2Hz group and EA 10Hz group received treatment for five weeks (02 acupuncture aplications per week). All the patients were evaluated pre-treatment and pos-treatment by polissomnography recordings and assessment of serotonin levels. The 5HT measurement was made with a HPLC-ED (Liquid Chromatografy coupled with Electrochemical Detection). MEASUREMENTS AND RESULTS: 1 – Immediate effect: when compared before and after treatment, the AHI (P=0,006; P=0,009), respiratory events (P=0,012; P=0,005), microarousals (P=0,046; P=0,05) and mean O2 saturation (P=0,006; P=0,035) showed significant improvement in both the manual and electroacupuncture 10 Hz respectively. The apnea index (P=0,028) and the hipopneia index (P=0,046) showed significant improvement only in EA 10 Hz group. There were no significant changes in the electroacupuncture 2 Hz as well as in the control group when compared before and after (first and second for controls) PSG recordings. When compared each group and control group, AHI significantly decreased only in the EA 10 Hz. 2 – Mediate effect: When compared before and after treatment, sleep onset (P=0,011;P=0,005), AHI (P=0,011;P=0,006), apnea index (P=0,042;P=0,005), respiratory events (P=0,011;P=0,009) and microarousals (P=0,011;P=0,021 ) significantly improved in MA and EA 10 Hz respectively. Hipopnea-index (P=0,021) decreased only in the EA 10Hz. Latency for sleep onset (P=0,005;P=0,005) decreased in both EA 2Hz and control group. Except for this change, there were no other significant changes in EA 2 Hz, or in control group after treatment. When compared to the control group the only significant differences were AHI and microarousals that were decreased in EA 10 Hz group (P=0,004;P=0,008). As concerned to the levels of seric serotonin we could not evidence an involvement of this neurotransmitter (as measured in blood) with the immediate effects of acupuncture for OSHA (MA vs. controls [P=0,7674], EA 2 Hz vs controls [P=0,9849]) despite a tendency for a difference for EA 10 Hz as compared to controls (P=0,1042). With regard to an effect of mediate acupuncture in moderate OSHA we found that seric serotonin levels were signficantly different form controls for MA (P=0,0067) with a tendency for group EA 10 Hz (P=0,0984). The lack of more robust differences for seric serotonin levels might have been influcenced by a smaller numeber of subjects as that required for this sort of evaluations. Conclusions: MA and EA 10 Hz have greater efficacy as compared to EA 2 Hz in improving AHI and other respiratory events in patients with moderate OHSA. This effect was shown to hold for both in the immediate (1 acupuncture session) as in the mediate (10 sessions) acupuncture application. The preliminary serotonin results indicate a possible mechanistic link between acupuncture treatment and its beneficial effects for the treatment of patients with moderate OHSA.